1983
DOI: 10.1104/pp.72.4.925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photosynthetic Performance in Triazine-Resistant and Susceptible Biotypes of Amaranthus hybridus

Abstract: The rate of CO2 reduction in the S-triazine-resistant biotype of smooth pigweed (Amaranthus hybridus L.) was lower at all levels of irradiance than the rate of CO2 reduction in the susceptible biotype. The intent of this study was to determine whether or not the lower rates of CO2 reduction are a direct consequence of the same factors which confer triazine resistance. The quantum yield of CO2 reduction was 23 ± 2% lower in the resistant biotype of pigweed and the resistant biotype of pigweed had about 25% fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
2
5

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 18 publications
3
47
2
5
Order By: Relevance
“…The dynamic nature of these responses has led several to conclude that the primary effect of R is complex, involves more than one aspect of photosynthesis, and can be mitigated by other processes in the system (17,23). For example, it has been pointed out that decreased QA to QB electron transport in R plants is more rapid than the normally rate-limiting oxidation of plastoquinol (4,24), whereas other studies indicate that this step may be rate limiting (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic nature of these responses has led several to conclude that the primary effect of R is complex, involves more than one aspect of photosynthesis, and can be mitigated by other processes in the system (17,23). For example, it has been pointed out that decreased QA to QB electron transport in R plants is more rapid than the normally rate-limiting oxidation of plastoquinol (4,24), whereas other studies indicate that this step may be rate limiting (20).…”
mentioning
confidence: 99%
“…Several studies have shown lower A rates in R Amaranthus hybridus (1) and Senecio vulgaris (15,24) relative to S plants. Beversdorf et al (6) found lower R plant whole plant yields in field evaluations of Brassica napus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The photosynthetic rate and biomass accumulation of greenhouse grown susceptible and resistant S. vulgaris biotypes were measured 28, 35, 42, 50, 57, and (17). PSII efficiency in the use of separated charge for oxygen evolution and electron transport is lower in resistant biotypes (12, 17) which explains the lower quantum yields characteristic of triazine resistant biotypes (5,13,15,17,19).As expected from the reduced photosynthetic potential of triazine resistant biotypes, several studies have shown that in the absence of triazine herbicides, resistant biotypes produce less biomass than susceptible biotypes. In Amaranthus spp., B. napus, Chenopodium album, and Senecio vulgaris, resistant biotypes accumulated less biomass and produced less seed than susceptible biotypes in competitive and noncompetitive conditons (7,8,11,29).…”
mentioning
confidence: 99%
“…However, the binding site alteration also slows by 10-fold the normal electron transfer between Qa and Qb (5). Slow electron flow between Qa and Qb has been suggested as the cause of the reduction in photon yield observed in resistant plants (14,15,19), and has been cited as the ultimate cause of decreased maximum photosynthesis in resistant plants ( 16).…”
mentioning
confidence: 99%